Residue from the production of Pochonia chlamydosporia in the development of lettuce seedlings and plants - Viggiano, José Ricardo; Freitas, Leandro Grassi de; Ferreira, Paulo Afonso (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effect of a by‑product of the production process of Pochonia chlamydosporia var. chlamydosporia in the development of lettuce seedlings and plants. This by‑product, a residue made up of rice containing propagules of the fungus, was added at different concentrations (0, 2, and 4% volume of residue:volume of substrate) to three types of substrates for seedlings (formulated, commercial, and coconut fiber). Lettuce seeds were sown in polystyrene trays containing the different substrates enriched with the residue. The lettuce seedlings were transplanted into pots containing soil and sand substrate at the proportion 1:1 (v:v), 28 days after sowing. All types of substrates and residue levels showed a significant interaction for all variables related to the development of lettuce seedlings and plants. The highest development of seedlings occurred in the control treatment (no residue) of the substrates. However, after transplanting the seedlings into the pots, the residue levels of up to 4 and 2% v:v – in the formulated and commercial substrates, respectively – promoted the highest plant growth. The use of up to 2% v:v of the residue on the formulated and commercial substrates is viable and does not affect the development of lettuce plants.